2015
DOI: 10.1162/jocn_a_00689
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographically Significant Concepts: More Episodic than Semantic in Nature? An Electrophysiological Investigation of Overlapping Types of Memory

Abstract: A common assertion is that semantic memory emerges from episodic memory, shedding the distinctive contexts associated with episodes over time and/or repeated instances. Some semantic concepts, however, may retain their episodic origins or acquire episodic information during life experiences. The current study examined this hypothesis by investigating the ERP correlates of autobiographically significant (AS) concepts, that is, semantic concepts that are associated with vivid episodic memories. We inferred the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 83 publications
(131 reference statements)
4
43
0
Order By: Relevance
“…showing that this ERP component can be evoked by autobiographical in addition to (nonpersonal) laboratory material. This was confirmed in a study by Renoult et al (2015), in which the LPC was found to be increased for famous names that were associated with autobiographical episodes by the participants. Importantly, results from this study also illustrate that this ERP component is sensitive to the most automatic aspects of episodic retrieval, as the presence of associated episodes was only assessed after the experiment, and was thus incidental to task performance.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…showing that this ERP component can be evoked by autobiographical in addition to (nonpersonal) laboratory material. This was confirmed in a study by Renoult et al (2015), in which the LPC was found to be increased for famous names that were associated with autobiographical episodes by the participants. Importantly, results from this study also illustrate that this ERP component is sensitive to the most automatic aspects of episodic retrieval, as the presence of associated episodes was only assessed after the experiment, and was thus incidental to task performance.…”
Section: Introductionsupporting
confidence: 64%
“…Further studies are thus needed to specify how the neural correlates of memories of repeated events differ from those of unique events. As we note below, one possible factor to explain a certain inconsistency in the difference between unique and repeated events is that it is possible that some memories of repeated events evoked recollective experiences, while others do not (Renoult, et al, 2015) Three broad conceptualizations of personal semantics were proposed in our review : 1) that personal semantics could be a sub-domain of semantic memory, 2) that declarative memory could be organized according to a continuum of abstraction from abstract/acontextual to personal/contextual and 3) that PS, semantic and episodic memory could involve a different weighting of different component processes (see Cabeza & Moscovitch, 2013 on process-specific alliances). While the present results cannot be used to definitively decide between these views, a number of observations can be made.…”
Section: Autobiographical Facts Versus Repeated Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is reason to believe that concepts with personal significance engage more than just the semantic memory system. Recent work suggests that these concepts may be more similar to episodic memory than general semantic memory (for a review, see Renoult, Davidson, Palombo, Moscovitch, & Levine, 2012), in that autobiographically significant concepts automatically activate related episodes in memory (Westmacott, Black, Freedman, & Moscovitch, 2004; Westmacott & Moscovitch, 2003) and evoke a neural signature more similar to episodic than semantic memory (Renoult et al, 2015, 2016). Thus, the current effects could be partly or entirely driven by episodic memory, with the names of familiar places activating related details of past episodes, including people who were there, in a relatively automatic (and potentially subconscious) manner.…”
Section: Discussionmentioning
confidence: 99%